Respuesta :

Space

Answer:

g = 1, 3

General Formulas and Concepts:

Pre-Algebra

  • Equality Properties

Algebra I

  • Terms/Coefficients
  • Factoring
  • Solving quadratics

Step-by-step explanation:

Step 1: Define

Identify

g² - 4g = -3

Step 2: Solve for g

  1. [Addition Property of Equality] Add 3 on both sides:                                     g² - 4g + 3 = 0
  2. Factor:                                                                                                                (g - 1)(g - 3) = 0
  3. Solve:                                                                                                                 g = 1, 3